Self‐reported experiences and consequences of unfair treatment by police*. Issue 2 (15th January 2021) - Dennison, Christopher R.; Finkeldey, Jessica G.
Abstract: This study uses data from the most recent wave of the National Longitudinal Study of Adolescent to Adult Health (wave V of Add Health) to examine the predictors of experiencing unfair treatment by police. It also considers the degree to which unfair police treatment is associated with a range of social‐psychological and behavioral outcomes in adulthood, including depressive symptoms, self‐efficacy, suicide ideation, and drug use. Finally, this study examines whether any of the relationships between unfair police treatment and adult outcomes differ by race and ethnicity. Most broadly, results suggest that the odds of reporting ever experiencing unfair treatment by police are disproportionately higher among minorities (and more specifically non‐Latino Blacks), men, and those from lower socioeconomic backgrounds. Furthermore, such experiences are detrimental to all of the social‐psychological and behavioral outcomes in adulthood, even after accounting for the differences in who is most likely to experience unfair police treatment via propensity score methods. Lastly, some of these consequences seem to be more pronounced among non‐Latino Whites compared with non‐Latino Blacks, which we believe is attributable to the unfortunate reality that unfair police contact continues to be a normative life‐course event for Black people in the United States.